Rare variants in complement system genes associate with endothelial damage after pediatric allogeneic hematopoietic stem cell transplantation - Leimi, Lilli; Koski, Jessica R.; Kilpivaara, Outi; Vettenranta, Kim; Lokki, A. Inkeri; Meri, Seppo (Frontiers in Immunology, 2023)
Complement system has a postulated role in endothelial problems after hematopoietic stem cell transplantation (HSCT). In this retrospective, single-center study we studied genetic complement system variants in patients with documented endotheliopathy. In our previous study among pediatric patients with an allogeneic HSCT (2001HSCT ( -2013) ) at the Helsinki University Children´s Hospital, Finland, we identified a total of 19/122 (15.6%) patients with vascular complications, fulfilling the criteria of capillary leak syndrome (CLS), veno-occlusive disease/sinusoidal obstruction syndrome (VOD/SOS) or thrombotic microangiopathy (TMA). We performed whole exome sequencing (WES) on 109 patients having an adequate pre-transplantation DNA for the analysis to define possible variations and mutations potentially predisposing to functional abnormalities of the complement system. In our data analysis, we focused on 41 genes coding for complement components. 50 patients (45.9%) had one or several, nonsynonymous, rare germline variants in complement genes. 21/66 (31.8%) of the variants were in the terminal pathway. Patients with endotheliopathy had variants in different complement genes: in the terminal pathway (C6 and C9), lectin pathway (MASP1) and receptor ITGAM (CD11b, part of CR3). Four had the same rare missense variant (rs183125896; Thr279Ala) in the C9 gene. Two of these patients were diagnosed with endotheliopathy and one with capillary leak syndrome-like problems. The C9 variant Thr279Ala has no previously known disease associations and is classified by the ACMG guidelines as a variant of uncertain significance (VUS). We conducted a gene burden test with gnomAD Finnish (fin) as the reference population. Complement gene variants seen in our patient population were investigated and Total Frequency Testing (TFT) was used for execution of burden tests. The gene variants seen in our patients with endotheliopathy were all significantly (FDR < 0.05) enriched compared to gnomAD. Overall, 14/25 genes coding for components of the complement system had an increased burden of missense variants among the patients when compared to the gnomAD Finnish population (N=10 816). Injury to the vascular endothelium is relatively common after HSCT with different phenotypic appearances suggesting yet unidentified underlying mechanisms. Variants in complement components may be related to endotheliopathy and poor prognosis in these patients.